A Linguistic Analysis of The Use of Humour in Adébáyò̩ Fálétí’s Writings - Dayo Akanmu; Francis Yede (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This study discussed strategies of humour in Adébáyọ̀ Àkàndé Fálétí’s writings. It interrogates how humour as a universal human interactional phenomenon is used to particularly entertain, checkmate human excesses and chastise societal ills in a mild manner. It is noted that among the living things only human beings laugh and humour excites laughter but it is not every humour that leads to laughter. Therefore, for humour to be effectively appreciated, it must be properly situated in its social context. The theoretical framework for this study is based on Thomas Veatch postulation of humour as a phenomenon made up of congruous and incongruous elements of socially typical and infringement of the prejudiced ethical standard. This framework is adopted to study Faleti’s use of humour to entertain, criticize human actions and chastise societal ills. It was out that humour as a form of lampoon is used euphemistically or ironically not as a means to destroy the society but to improve it. Faleti uses humour as an effective weapon of criticism and a subtle source of laughter to entertain the audience and to curb aberrations in the society. Humour in Faleti’s writings is used in a calm and amusing manner and the end result is laughter, although beneath the laughter is the lampoon of social misdemeanours concealed in the use of light-hearted constructions. Faleti has succeeded in espousing various methods of coping with serious and tense situation through the use of strategies of humour.